PENTINGNYA HUMAS PADA STAKE HOLDER INSTITUSI PENDIDIKAN - Maskur, Maskur (Kopertais Wilayah X Jawa Tengah, 2014)
AbstractResearch on the implementation of public relations management in SMP Islam Al - Azhar 14 Semarang has a goal to find a variety of public relations programs at SMP Islam Al - Azhar 14 Semarang , knowing the implementation of public relations programs on SMP Islam Al - Azhar 14 Semarang as well as to determine the various factors that affect the implementation of the program public relations and the implications of the implementation of the management program of public relations for the Islamic Al - Azhar SMP 14 Semarang .The method used is descriptive research with a qualitative evaluation approach . Where research is directed to provide a detailed overview of the various programs implemented in the junior public relations Islam Al - Azhar 14 Semarang . The study is directed to look at the success rate of public relations programs that have been planned , so as to see the suitability of the program emphasized the implementation of public relations programs . By looking at the level of implementation of public relations programs , it will be able to see a variety of factors that encourage , or factors that mengambat implementation of public relations programs at SMP Islam Al - Azhar 14 Semarang . The most important thing that is examined in this study also aimed to see dampk arising from the absence of the implementation of public relations management , the impact of both positive and negative impacts of the implementation of public relations management .The results showed that the public relations program at SMP Islam Al - Azhar 14 Semarang has distinguished between internal and external programs . Internally directed public relations programs to build a harmonious ties between large families SMP Islam Al - Azhar 14 Semarang , while externally directed public relations programs to build a positive public image of the institution , so that pretty much diverse activities , developing a kind of activity the ability of teachers , development of religious , braid premises cooperation of various parties as well as improving the quality of learning activities are carried out . The implementation of public relations programs both internally and externally is quite in accordance with the planned public relations program . The factors that drive the implementation of which is a form of public relations management frinchese driving school set school standards with standard central schools , foundation support and the support of principals who strongly support the implementation of public relations management in SMP Islam Al - Azhar 14 Semarang . While the factors that hinder the implementation of the separation of the management of public relations is not yet in the public relations vice principal public relations , media and public relations ability of users who have not been competent in the use of information presented by the publicity department . The impact of the implementation of public relations major manejemen is a positive image of the institution in the eyes of the public the better .Keywords: public relations program , implementation of public relations programs